KAJIAN BAHAYA KEBAKARAN HUTAN DI KABUPATEN NGANJUK - Naryanto, Heru Sri; Wisyanto, Wisyanto (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2020)
ABSTRACTThe Nganjuk District is mostly planted by forests, both protection forests and production forests with a total area of 20 333.00 ha. Forest and land fires often occur in Nganjuk District, which causes economic and environmental losses. Forest and land fires often cause haze disasters that can disrupt the activities and health of surrounding communities. The forest and land fire hazard map is needed. Making a forest and land fire hazard map of Nganjuk District is carried out with consideration of various parameters, namely: rainfall, land use, altitude, and type of forest. The analysis was carried out using spatial analysis with a scoring system of influential parameters, and from the results of the analysis 3 (three) classifications of fire hazard-prone areas were determined, namely: high hazard, moderate hazard, and low hazard. The five (5) biggest sub-districts included in the forest and high land fire hazard zones in Nganjuk District are the sub-districts: Rejoso, Lengkong, Ngluyu, Gondang, and Jatikalen. Zoning maps of forest and land fire hazards in Nganjuk District are urgently needed in the framework of mitigation, adaptation and disaster management of forest and land fires, as well as sustainable development planning in Nganjuk District. Keywords: Nganjuk, forest and land fires, hazard zone map, mitigation. ABSTRAKKawasan Kabupaten Nganjuk hutan banyak ditumbuhi oleh hutan, baik hutan lindung maupun hutan produksi dengan luas total 20 333.00 ha. Kebakaran hutan dan lahan sering terjadi di Kabupaten Nganjuk, yang menyebabkan kerugian ekonomi dan lingkungan. Kebakaran hutan dan lahan seringkali menyebabkan bencana asap yang dapat mengganggu aktivitas dan kesehatan masyarakat sekitar. Peta zonasi bahaya kebakaran hutan dan lahan sangat diperlukan. Pembuatan peta bahaya kebakaran hutan dan lahan Kabupaten Nganjuk dilakukan dengan pertimbangan berbagai parameter, yaitu: curah hujan, tataguna lahan, ketinggian tempat, dan jenis hutan. Analisis dilakukan dengan menggunakan analisis spasial dengan sistem skoring dari parameter yang berpengaruh, dan dari hasil analisis akan ditetapkan 3 (tiga) klasifikasi daerah rawan bahaya kebakaran yaitu: bahaya tinggi, bahaya sedang, dan bahaya rendah. Lima (5) kecamatan terbesar yang termasuk zona bahaya kebakaran hutan dan lahan tinggi di Kabupaten Nganjuk adalah kecamatan-kecamatan: Rejoso, Lengkong, Ngluyu, Gondang, dan Jatikalen. Peta zonasi bahaya kebakaran hutan dan lahan di Kabupaten Nganjuk sangat diperlukan dalam rangka mitigasi, adaptasi dan penanggulangan bencana kebakaran hutan dan lahan, serta perencanaan pembangunan berkelanjutan di Kabupaten Nganjuk. Kata kunci: Nganjuk, kebakaran hutan dan lahan, peta zonasi bahaya, mitigasi.